Actionable driver DNA variants and fusion genes can be detected in archived cytological specimens with the Oncomine Dx Target Test Multi‐CDx system in lung cancer. Issue 9 (19th April 2021) - Amemiya, Kenji; Hirotsu, Yosuke; Nagakubo, Yuki; Mochizuki, Hitoshi; Higuchi, Rumi; Tsutsui, Toshiharu; Kakizaki, Yumiko; Miyashita, Yoshihiro; Oyama, Toshio; Omata, Masao
Abstract : BACKGROUND: Molecular testing is critical for identifying actionable variants in lung cancer for precision medicine. When tumor tissue samples are unavailable, archived cytological specimens (ACSs) can be used. The authors examined whether oncogenic variants could be accurately detected in ACSs versus paired formalin‐fixed, paraffin‐embedded (FFPE) tumor tissues with in vitro diagnostic tests. METHODS: The authors collected 18 ACSs and 15 FFPE tissues from 15 patients with lung cancer and investigated genomic profiles with the Oncomine Dx Target Test Multi‐CDx system, which is an integrated next‐generation sequencing platform that comprehensively examines 4 companion diagnostic target genes (epidermal growth factor receptor [ EGFR ]; B‐Raf proto‐oncogene, serine/threonine kinase [ BRAF ]; anaplastic lymphoma kinase [ ALK ]; and ROS proto‐oncogene 1, receptor tyrosine kinase [ ROS1 ]). They compared the quantity and quality of extracted nucleic acids, the sequencing quality control (QC), and the detected variants between ACSs and FFPE tissues. RESULTS: The total amount of DNA and RNA obtained from 1 slide was higher in FFPE tissues than ACSs. The RNA integrity number was higher in ACSs. There were no differences in sequencing QC between ACSs and FFPE tissues. A total of 21 variants, including EGFR mutations and ALK and ROS1 fusion genes, were detected in both ACSs and FFPE tissues with 100% concordance. CONCLUSIONS: ACSs can be a feasible alternative with which to identify actionable mutations and fusion genes via the Oncomine Dx Target Test Multi‐CDx system. Abstract : All detected variants are found in both archived cytological specimens (ACSs) and formalin‐fixed, paraffin‐embedded tissues. ACSs may provide new alternative materials for DNA‐ and RNA‐based molecular testing using next‐generation sequencing.